IMPACT OF MICROMETASTASIS AND ISOLATED TUMOR CELLS FOUND ON SENTINEL LYMPH NODES IN EARLY BREAST CANCER - Pellizzon, Antonio Cassio Assis (Mastology, 2018)
The presence of axillary lymph node metastases is one of the most important prognostic factors in breast cancer and it is often used to guide locoregional and systemic therapy decisions. The question of whether axillary dissection (AD) can be safely omitted in patients with early breast cancer when isolated tumor cells (ITC) or micrometastasis is found in the sentinel node remains a controversial issue in the literature. On the basis of current evidence, AD could probably be safely omitted when micrometastasis or ITC are found. On making this decision, as micrometastasis and ITC are a sign of a biologically different disease, adjuvant radiotherapy and the adjuvant systemic treatment need to be considered.